Democrats' 1916 Tariff Commission: Responding to Dumping Fears and Illustrating the Consumer Costs of Protectionism - Schnietz, Karen (Business History Review, 1998)
The 1916 Tariff Commission, created to provide expert analyses of tariffs, is an example of Progressive-Era reliance on technical analysis. However, the Commission was motivated not only by a desire to improve technical understanding of tariffs, but also by distinctly political goals. President Woodrow Wilson and Treasury Secretary McAdoo adopted this Republican invention in response to pressure to prevent potential foreign “dumping” after the First World War. Congressional Democrats supported the Tariff Commission for this and an additional reason: they hoped Commission analyses of the consumer welfare costs of protectionism would undermine future electoral support for Republican high-tariff candidates.
Keywords: Business History and gender